Soil microbial functional diversity is primarily affected by soil nitrogen, salinity and alkalinity in wetland ecosystem - Zhu, Meng-Yuan; Liu, Zhen-Di; Song, Yan-Yu; Wang, Xian-Wei; Yuan, Jia-Bao; Li, Meng-Ting; Lou, Yan-Jing; Gao, Zhen-Ling; Song, Chang-Chun (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2024)
Wetland ecosystems, recognized as important carbon sinks, face challenges due to climate change. Although wetland soil microorganisms play a major role in the wetland carbon cycle, the mechanisms influencing their spatial distribution remain elusive. Here, we investigate the impact of soil properties on the spatial distribution of soil microorganisms across five saline-alkali wetlands (Xianghai [XH], Niuxintaobao [NX], Momoge [MMG], Zhalong [ZL], and Halahai [HLH]) within the Songnen Plain, China. We utilized the Biolog-ECO method to assess the carbon metabolic activity, microbial diversity, and carbon source utilization preference of soil microorganisms. Using the structural equation model, we analyzed factors influencing microbial carbon metabolic activity and microbial diversity. Results indicate that southern wetlands harbor soil microbial communities exhibiting higher carbon metabolic activity, Shannon index, and substrate richness, compared to their northern counterparts. Specifically, soil microorganisms in NX and XH wetlands demonstrate a preference for labile organic carbon, whereas those in HLH and ZL wetlands preferred to use recalcitrant carbon. Furthermore, soil microbial carbon metabolic activity is primarily regulated by soil total nitrogen content, whereas soil microbial diversity is primarily regulated by soil salinity and alkalinity. Our findings revealed the distribution characteristics and influencing factors of soil microorganisms in the Songnen Plain wetland, contributing to understanding the maintenance mechanism of wetland carbon sink function. [Display omitted] •Soil microbial C metabolic activity was higher in the south wetland of Songnen Plain.•Soil microbes preferred to use recalcitrant C in the north wetland of Songnen Plain.•Soil microbial C metabolic activity was primarily affected by soil nitrogen content.•Soil microbial functional diversity was primarily regulated by soil salinity and alkalinity.